Time Domain Reflection Method To Detect Copper Wire Micro Crack Weld Defect - Robin, Ong Su Kiat (2016)
Structural integrity of wire bonding interconnection is having a significant impact on the quality of microelectronic devices. Conventional electrical test methodology is unable to detect 1 to 20 m of cracks that exists in wire bond stitch weld. This micro crack has becomes prominent in Power MOSFET Molded Leadless Package (MLP) with copper wire of 38 m in diameter and 800 m long. In this research, total 1368 units of Power MOSFETs was tested using a Credence ASL1000 tester. The aim of this research is to investigate an alternative methodology by establishing a comprehensive physical and simulation characterization technique namely Time Domain Reflectometry (TDR) to address this issue. Parameters that have been investigated included TDR input (frequency of 20 and 50 GHz and time domain between 10 to 23 psec) and output (reflection voltage from 0 to 250 mV and characteristic impedance) responses on the wire crack geometries (length from 1 to 20 m and crack area). 50 GHz TDR successfully detected 10, 50 and 90 % of crack size with physical length of 1, 4 and 10 m respectively. In order to complement with the TDR results, other non-destructive 2D & 3D X-ray Computed Tomography (CT) and destructive Scanning Electron Microscopy (SEM) characterization techniques have been used. Simulation of crack weld length and crack area has also been performed, in order to estimate the physical crack dimension without using the actual TDR instrument. Besides, a prediction of TDR response on both reflection voltage and impedance change have also been verified. Novelty of this work is on the non-destructive electrical test methodology that able to detect micro crack defect at wedge bond in a Power MOSFET gate wire. This effective technique offers up to physical dimension of 1 m and simulated dimension of 10 m comparing with other techniques. TDR has overcome the conventional test limitation and achieved a novel approach through the defined detection resolution for micro crack weld.